From Insecurity to Leadership: A Self-Esteem Enhancement Training for Nursing Students to Improve Job Readiness - Ekawati, Dessy; Nofalia, Ifa (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Nursing students often face psychological challenges before graduation, including low self-esteem, which may hinder their readiness to enter the workforce. This community service aimed to improve the self-esteem of eighth-semester nursing students through a structured training program to better prepare them for professional life. The training was conducted at the ITSKES ICME Jombang Hall in February 2025 and involved 82 students selected using total sampling. The one-day session included materials on self-concept reinforcement, motivational techniques, and job interview simulations. Evaluation was carried out using pre- and post-tests based on the Rosenberg Self-esteem Scale. The pre-test results showed that 34.1% of respondents had low self-esteem, 52.4% moderate, and 13.5% high. After the training, there was a significant increase: only 3.7% remained in the low category, 40.2% were moderate, and 56.1% had reached a high self-esteem level. The self-esteem enhancement training proved effective in increasing the confidence of nursing students and is recommended as a strategy to strengthen soft skills in preparation for entering the workforce.